Chapter 3 - Application of metagenomics in the field of biotechnological conversion of lignocellulosic residues - Santos, Andréia O. (2024)
Several studies have demonstrated how metagenomic libraries provide a vast pool of new genes encoding biotechnology products of interest from various environmental samples including soil, compost, rumen, and termite gut, among others. Despite that, there are just few reports that explore, through metagenomic approaches, the biotechnological potential of lignocellulosic residues. This chapter highlights the potential of metagenomic approaches for the development of a green and circular economy based on the efficient bioconversion of underexploited lignocellulosic residues into value-added biocompounds.